A Research on Some Challenges of Tourism Industries: A Case Study of Kashmir Valley: Understanding the Impact of Violent Conflicts on Tourism in Kashmir Valley (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Tourism plays a vital role in economic development of a number of countries across the globe. Kashmir knows for its extravagant and breath taking beauty throughout the world, Kashmir has aptly been described as ‘The Paradise on Earth’. Kashmir is second to no place in the world as far as its natural beauty and rich culture heritage is concerned. However the recent decades have proved challenging for nations due to emergence and escalation of a wide variety of violent conflicts around the state. The continual political uncertainty in general and the two decades long armed conflict in particular has unexceptionally impacted every socio-economic activity in Kashmir. Turmoil in the state, particularly of last two decades, hindered the smooth growth of the tourism and has discouraged most of the travellers from visiting India’s most popular tourist destination. Add to this it also not only tourism but also indirectly the economic activities related to tourism.